2020
DOI: 10.7554/elife.62210
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of young and old mouse hematopoietic stem cells and their progenitors reveals post-transcriptional regulation in stem cells

Abstract: The balance of hematopoietic stem cell (HSC) self-renewal and differentiation is critical for a healthy blood supply; imbalances underlie hematological diseases. The importance of HSCs and their progenitors have led to their extensive characterization at genomic and transcriptomic levels. However, the proteomics of hematopoiesis remains incompletely understood. Here we report a proteomics resource from mass spectrometry of mouse young adult and old adult mouse HSCs, multipotent progenitors and oligopotent prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 94 publications
6
30
0
Order By: Relevance
“…This suggests that while mRNA-based analysis can provide an accurate picture of the cells' potential, it is an inadequate predictor of the actual cellular phenotype in quiescent HSCs. In line with this, the correlation between protein and mRNA expression is particularly poor in HSCs, although that observed in MPPs is only slightly higher (Zaro et al, 2020). Comparison of protein data generated in our lab of fetal and adult lymphomyeloid multipotent progenitors (LMPPs) (Jassinskaja et al, 2021) to a recently published RNAseq dataset of the same populations (Symeonidou et al, 2021) further highlights that correlation between proteome and transcriptome is mediocre at best even in progenitors downstream of HSCs (r = 0.4216).…”
Section: Post-transcriptional Regulation In Fetal and Adult Hematopoi...supporting
confidence: 71%
See 1 more Smart Citation
“…This suggests that while mRNA-based analysis can provide an accurate picture of the cells' potential, it is an inadequate predictor of the actual cellular phenotype in quiescent HSCs. In line with this, the correlation between protein and mRNA expression is particularly poor in HSCs, although that observed in MPPs is only slightly higher (Zaro et al, 2020). Comparison of protein data generated in our lab of fetal and adult lymphomyeloid multipotent progenitors (LMPPs) (Jassinskaja et al, 2021) to a recently published RNAseq dataset of the same populations (Symeonidou et al, 2021) further highlights that correlation between proteome and transcriptome is mediocre at best even in progenitors downstream of HSCs (r = 0.4216).…”
Section: Post-transcriptional Regulation In Fetal and Adult Hematopoi...supporting
confidence: 71%
“…Similarly to normal hematopoiesis, proteome level characterization of the molecular events governing MLL-FPmediated leukemogenesis in infants and adults remains scarce. This is of particular concern considering the discrepancies between proteome and transcriptome in HSPCs outlined above (Cabezas-Wallscheid et al, 2014;Haas et al, 2015;Jassinskaja et al, 2017;Zaro et al, 2020), as well as the numerous reports showing even further decrease in mRNAprotein correlation upon malignant transformation (Yang et al, 2020). Indeed, the expression of genes associated with metabolic rewiring, a key hallmark of cancer, was recently shown to be regulated post-transcriptionally in primary human AML (Raffel et al, 2017(Raffel et al, , 2020.…”
Section: Molecular Features Of Mllr Infant and Adult Leukemiamentioning
confidence: 99%
“…Zaro et al. ( 102 ), for example, used dda-PASEF to study the proteomes of young and old mouse hematopoietic stem cells and their progenitors, including rare cell types of which only few thousands to ten thousands can be purified from a single mouse. Analyzing the proteomes of fluorescence-activated cell sorting–purified human β-cells, Fu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we expect researchers to leverage the intrinsic sensitivity of the technology. Zaro et al 104 , for example, used dda-PASEF to study the proteomes of young and old mouse hematopoietic stem cells and their progenitors, including rare cell types of which only few thousands to ten thousands can be purified from a single mouse. Analyzing the proteomes of FACS-purified human β-cells, Fu et al 105 revealed a link between glucose metabolism and cellular sensitivity to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular programs that govern the functional differences between fetal and adult hematopoiesis have predominantly been investigated at the transcript level in HSCs (Beerman et al, 2014;Manesia et al, 2017;McKinney-Freeman et al, 2012). However, since post-transcriptional regulation has a vital role in HSPC function, both under normal and non-homeostatic conditions (Haas et al, 2015;Jassinskaja et al, 2017;Klimmeck et al, 2012;Raffel et al, 2020;Sun et al, 2018;Zaro et al, 2020), comprehensive protein-level characterization is essential for delineating the molecular mechanisms regulating the functional variation of hematopoiesis during normal development and disease. In our previous work, we established that the proteome of Lin À Sca-1 + cKit + (LSK) HSPCs undergoes extensive ontogenic remodeling that is reflective of the divergent nature of fetal and adult hematopoiesis (Jassinskaja et al, 2017).…”
Section: Introductionmentioning
confidence: 99%